Observations about Lithuanian state-level maturity examination in mathematics - Karikovas, Erikas; Miežys, Vytautas (Lietuvos matematikos rinkinys, 2021)
The article presents several observations about the examination papers of the state-level Maturity Examinations in Mathematics in the years 2014–2021 in Lithuania. Some inaccuracies were observed in the appendix of the paper titled ``Mathematical formulas'', in the wordings of the problems. Also the issue of proof problems in the examination is discussed. The purpose of these observations is to draw attention to areas for improvement in the examination system. The article presents the subjective opinion of the authors.
Keywords: state-level maturity examination in mathematics; mathematics education